1999
DOI: 10.1029/1998gb900019
|View full text |Cite
|
Sign up to set email alerts
|

Land use change and biogeochemical controls of nitrogen oxide emissions from soils in eastern Amazonia

Abstract: Abstract. The objectives of this study were (1) to determine the effects of land use change on N oxide fluxes from soil in seasonally dry, eastern Amazonia and (2) evaluate the "hole-in-the-pipe" model in a field setting where N availability varies among land uses and soil moisture varies among seasons. We measured N oxide flux from an old-growth forest, a 20-year-old secondary forest, an active pasture, and a degraded pasture. We also measured soil water content, soil inorganic N stocks, net N mineralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
309
16
28

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 306 publications
(401 citation statements)
references
References 45 publications
48
309
16
28
Order By: Relevance
“…It is important to note that hole-in-the-pipe type modeling is ongoing at many sites around the world, providing many opportunities for comparison and synthesis (Verchot et al 1999, Davidson et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that hole-in-the-pipe type modeling is ongoing at many sites around the world, providing many opportunities for comparison and synthesis (Verchot et al 1999, Davidson et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…[11] We calculated the minimum significant flux (a = 0.05 [Hutchinson and Livingston, 1993;Verchot et al, 1999;Ishizuka et al, 2005b]) from verification of each chamber flux. The minimum flux considered significantly different from zero was 37 mg N m À2 d À1 .…”
Section: Discussionmentioning
confidence: 99%
“…[20] Annual N 2 O emissions from secondary forest soils (0.33 kg N ha À1 ) are low relative to other tropical forests; e.g., tropical forest emissions are estimated at 0.01 -7.68 kg N ha À1 [Breuer et al, 2000] and Amazon secondary forests at 0.94 kg N ha À1 [Verchot et al, 1999] or 0.80 kg N ha À1 [Palm et al, 2002]. These low secondary forest emissions are comparable to those observed at primary forests in central Sumatra (0.13 kg N ha À1 and 0.39 kg N ha À1 [Ishizuka et al, 2002]), but relatively low compared to emissions from southern Sumatra forests (1.47 and 1.80 kg N ha À1 at sites showing high WFPS (90 -100% [Verchot et al, 2006]) and montane forests in central Sulawesi (0.29, 1.01, and 1.11 kg N ha À1 [Purbopuspito et al, 2006]).…”
Section: Conversion To Acacia Plantations Might Boost N 2 O Flux Frommentioning
confidence: 99%
“…For example, a laboratory study showed an optimum soil moisture of about 20% WFPS (Yang and Meixner, 1997), but in another study conducted in saline sodic soil of northeastern China, maximum NO fluxes was observed at approximately 9.5%e18% WFPS (Yu et al, 2008). The optimum value was even discovered to be approximately 50% WFPS in a seasonally dry forest of the eastern Amazon (Verchot et al, 1999). In this study, the optimum soil moisture for black soil NO emission was approximately 25.7%.…”
Section: Effects Of Soil Moisture and Temperature On No Emissionsmentioning
confidence: 99%
“…Many studies have shown that an optimum soil moisture does exist for soil NO emissions (Otter et al, 1999;Verchot et al, 1999;Yang and Meixner, 1997;Yu et al, 2008), but the value varied with soils. For example, a laboratory study showed an optimum soil moisture of about 20% WFPS (Yang and Meixner, 1997), but in another study conducted in saline sodic soil of northeastern China, maximum NO fluxes was observed at approximately 9.5%e18% WFPS (Yu et al, 2008).…”
Section: Effects Of Soil Moisture and Temperature On No Emissionsmentioning
confidence: 99%